Beyond Boundaries: A Feminist Critique of Oppression in the Age of Anthropocene - Ehsan, Bazila (Integrated Journal for Research in Arts and Humanities, 2024)
Anthropocene, marked by unprecedented environmental transformations due to human activities, provides a poignant backdrop to examine the interplay between gender, ecology, and exploitation. Ecofeminism, as a theoretical framework, serves as a powerful lens to analyze these complex relationships. The inquiry extends beyond conventional boundaries, traversing ecological, social, and cultural dimensions to unravel the ways in which patriarchal structures perpetuate exploitation in both human and environmental contexts. This paper would attempt to delve into the interdisciplinary exploration of ecofeminism within the context of the Anthropocene, a geological epoch defined by profound human impact on the Earth's ecosystems. The study would seek to examine the intricate connections between man’s exploitation of nature and women, bringing forth a nuanced understanding of the dynamics at play. The exploration would begin by discussing the foundations of ecofeminism, acknowledging its roots in environmental ethics and feminist thought. The study would then navigate through historical and contemporary perspectives, shedding light on instances where women and nature have been utilized and exploited as resources for unchecked human consumption and economic gain. Through an ecofeminist lens, the research would look into how patriarchal ideologies perpetuate a cycle of exploitation, further exacerbated by the Anthropocene's accelerated environmental degradation. The analysis underscores the urgency of recognizing the interconnectedness of these issues, proposing a call to action for transformative approaches to gender relations, ecological stewardship, and societal structures. By going "beyond boundaries," the study would seek to bridge gaps between disciplines, fostering a holistic understanding of the intricate web of exploitation that characterizes the Anthropocene. In conclusion, this interdisciplinary exploration would illuminate the dynamic intersections of ecofeminism and the Anthropocene, offering insights that go beyond conventional boundaries to contribute to a more profound comprehension of the challenges posed by human exploitation of both women and nature in this era of unprecedented environmental change.